The Urgency of Arabic Language in Branding Strategy Halal Tourism in Aceh Province - Supianudin, Asep; Khomisah, Khomisah; Setiyadi, Alif Cahya (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
One of the points in the branding strategy is promotion, which is identical to the language media used, including halal tourism branding. Become the main sector in promoting halal tourism. This research aims to describe halal tourism branding in Aceh province and see the urgency of Arabic in promoting halal tourism in Aceh province. The research method used is field research with qualitative, the data collection technique used is interviews with several informants, in this connection the head of the Banda Aceh and Aceh Besar Tourism Office, travel agents, and the community in the area that is the locus study. The research results show that first there is still a gap between the concept of halal tourism and the reality of its implementation the rules for implementation have not yet reached the wider community. Therefore, the local community does not understand halal tourism, the location of halal tourist attractions, the benefits of halal tourism for the local community, and the applicable rules regarding halal tourism in Aceh. Second, in branding halal tourism in Aceh province, it is necessary to develop a smartphone application that focuses on the use of Arabic as a promotional medium as well as a communication medium, especially now that the global market has entered the industrial revolution 5.0, where technological development is a necessity.